Genetic analysis in a lettuce diallel - Lédo, Francisco José da Silva; Casali, Vincente Wagner Dias; Cruz, Cosme Damião; Lêdo, Carlos Alberto da Silva (Pesquisa Agropecuaria Brasileira, 2001)
This work aimed to estimate genetic parameters in a lettuce diallel, according to the Jinks & Hayman's method. The experiment was carried out in a greenhouse, at the Universidade Federal de Viçosa, from October 20 to December 12, 1996. The experimental design used was a randomized complete blocks, with three replications. Pots with 4,5 dm3 of substrate and one plant/pot (plot) were used. Six lettuce cultivars and their respective F1 hybrids were evaluated. The following characters were evaluated: fresh matter of aerial part (FMAP); dry matter of aerial part (DMAP), leaves (DML) and roots (DMR); number of leaves/plant (NUL); and stem height (SH). Some evidences of epistasis were detected for DMAP, NUL and SH characters. In FMAP the variation of additive nature contributes predominantly to the genetic variability observed between parents and F1. The prevalence of dominance gene effects on the control of DML and DMR characters were evident. The estimates of genotypic determination coefficient on wide sense () in FMAP, DML and DMR were 0.84, 0.85 and 0.90, and restricted sense () 0.66, 0.45 and 0.49.